Resuscitation Aspects - Aslanidis, Theodoros (IntechOpen, 2017)
In an era of transition from "classic" Cardiopulmonary resuscitation (CPR) to assisted device-CPR or hemodynamic driven CPR, this book, published by InTechOpen, highlights some interesting aspects of resuscitation. Divided in three sections, the research presented emphasizes the details of resuscitation in special circumstances to possible future applications in the field. The authors offer us not only a "vigorous" review of the current literature but also a research road map for further advancement.